The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11606-014-2873-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Family and Caregiver Interventions on Patient Outcomes in Adults with Cancer: A Systematic Review

Abstract: Overall, there was low or insufficient evidence that family and caregiver interventions were superior to usual or active care. Variability in study populations and interventions made pooling of data problematic and generalizing findings from any single study difficult. Most of the included trials were of poor or fair quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 36 publications
1
59
0
1
Order By: Relevance
“…Existing interventions have typically demonstrated small to moderate effects on caregiver outcomes [36]. Further, there is little evidence that current caregiver- or family-interventions have a tangible impact on cancer survivor outcomes [37], possibly due in part to their limited effect on caregivers themselves. Targeting both cancer survivors and their spouses concurrently (e.g., by screening for and treating distress and depression in spouses as well as survivors) may be more effective at improving outcomes than either alone.…”
Section: Discussionmentioning
confidence: 99%
“…Existing interventions have typically demonstrated small to moderate effects on caregiver outcomes [36]. Further, there is little evidence that current caregiver- or family-interventions have a tangible impact on cancer survivor outcomes [37], possibly due in part to their limited effect on caregivers themselves. Targeting both cancer survivors and their spouses concurrently (e.g., by screening for and treating distress and depression in spouses as well as survivors) may be more effective at improving outcomes than either alone.…”
Section: Discussionmentioning
confidence: 99%
“…Interpersonal relationships are important in helping one to reintegrate successfully in the society when living with a stoma (Simmons et al., ). Family members have been commonly involved to enhance the effectiveness of interventions on patient outcomes in cancer patients (Griffin et al., ). Patients with poor interpersonal relationships tend to have poor stoma acceptance and reduced self‐efficacy in stoma care (Bekkers, van Knippenberg, van den Borne, & van Berge‐Henegouwen, ; Simmons et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Relatives might have more personal strength than patients, but new research has found a link between the level of anxiety in cancer patients and their relatives [41]. Moreover, a new systematic review did not find a convincing effect of family caregivers' supportive care in cancer [42]. Therefore, it is not recommended to rely fully on supportive care from relatives in the preoperative period.…”
Section: Discussionmentioning
confidence: 99%